2015
DOI: 10.1002/cncr.29314
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in noncoding PIWI‐interacting RNA and colorectal cancer risk

Abstract: The current findings reveal the possibility that piR-015551 may be generated from LNC00964-3, which may be involved in the development of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…One study showed that piRNAs are important determinants of CRC risk by binding to Piwi, and that genetic variants in piRNAs modulate CRC susceptibility. They identified seven piRNA SNPs in a search of all known human piRNAs available, and investigated the association between these seven SNPs and the risk of CRC [ 112 ]. The SNP rs11776042 in piR-015551, which may be generated from a type of lncRNA called LNC00964-3, was significantly associated with a decreased risk of CRC in an additive model; however, the protective effect was not significant after multiple comparison correction.…”
Section: Piwi-interacting Rnas In Crcmentioning
confidence: 99%
“…One study showed that piRNAs are important determinants of CRC risk by binding to Piwi, and that genetic variants in piRNAs modulate CRC susceptibility. They identified seven piRNA SNPs in a search of all known human piRNAs available, and investigated the association between these seven SNPs and the risk of CRC [ 112 ]. The SNP rs11776042 in piR-015551, which may be generated from a type of lncRNA called LNC00964-3, was significantly associated with a decreased risk of CRC in an additive model; however, the protective effect was not significant after multiple comparison correction.…”
Section: Piwi-interacting Rnas In Crcmentioning
confidence: 99%
“…Studies on the biological functions and possible clinical relevance of piRNAs in colorectal cancer (CRC) are still in the beginning. In 2015, Chu and colleagues (17) identified 7 common single-nucleotide polymorphisms in 9 known piRNAs. Further, they revealed that piR-015551 (DQ591252) may be generated from long noncoding RNA LNC00964-3, which is significantly downregulated in CRC tissues and may be involved in disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the association between piR59056, piR-54878, and piR-62701 and recurrence-free survival was also observed in colon cancer. Chu et al [91] observed that mRNA expression levels of LNC00964-3 which is an lncRNA that included the piR-015551 sequence were significantly lower in colorectal cancer (CRC) tissues than in corresponding normal tissues. The expression of piR-015551 was positively correlated with the LNC00964-3 expression levels, indicating that piR-015551 may be possibly generated from LNC00964-3, which may be involved in the development of CRC.…”
Section: Introductionmentioning
confidence: 99%